2022
DOI: 10.1007/s11356-022-19019-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ginsenoside Rg3 nanoparticles against Ehrlich solid tumor growth in mice

Abstract: Solid tumors are fairly common and face many clinical di culties since they are hardly surgically resectable and broadly do not respond to radiation and chemotherapy. The current study aimed to fabricate ginsenoside Rg3 nanoparticles (Rg3-NPs) and evaluate their antitumor effect against Ehrlich solid tumors (EST) in mice. Rg3-NPs were fabricated using whey protein isolates (WPI), maltodextrin (MD), and gum Arabic (GA). EST was developed by the injection of mice with Ehrlich ascites cells (2.5 x 10 6 ). The mic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 96 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Either Rg3 alone or Rg3 in combination with DDP suppressed the growth of colon tumor in nude mice (Lee et al, 2012b). Treatment with Rg3 decreased the tumor size of Ehrlich solid tumor in mice (El-Banna et al, 2022). In summary, increasing evidence has shown that Rg3 has therapeutic potential for the treatment of acute organ injuries and chronic diseases, which is worthy of further research.…”
Section: Overview Of the Therapeutic Potential Of Ginsenoside Rg3mentioning
confidence: 91%
See 2 more Smart Citations
“…Either Rg3 alone or Rg3 in combination with DDP suppressed the growth of colon tumor in nude mice (Lee et al, 2012b). Treatment with Rg3 decreased the tumor size of Ehrlich solid tumor in mice (El-Banna et al, 2022). In summary, increasing evidence has shown that Rg3 has therapeutic potential for the treatment of acute organ injuries and chronic diseases, which is worthy of further research.…”
Section: Overview Of the Therapeutic Potential Of Ginsenoside Rg3mentioning
confidence: 91%
“…Graphene oxide nanoparticle-loaded Rg3 promoted apoptosis and enhanced ROS generation to enhance photodynamic therapy of osteosarcoma ( Lu et al, 2021 ). Rg3 nanoparticles (Rg3-NPs) promoted apoptosis and improved oxidative stress states against Ehrlich solid tumor growth in mice ( El-Banna et al, 2022 ). Regarding tumorigenesis, abnormal expression of COX-2 and proinflammatory cytokines is associated with skin carcinogenesis ( Moon et al, 2020 ).…”
Section: Antioxidant and Anti-inflammatory Effects And Molecular Mech...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ginsenosides have gradually attracted the attention of researchers, and their role in reversing immune-suppressive TME has received special attention ( Sekar et al, 2022 ; Zhao et al, 2022 ). Increasing evidence shows that ginsenosides benefit the intestinal ecological environment of normal people and CRC patients and animals ( Hou et al, 2022 ; El-Banna et al, 2022 ; Lei et al, 2022 ). Clinical data show that CRC patients taking ginsenosides induce tumor cell cycle blockage and cell apoptosis ( Li et al, 2020 ), reduce cancer-induced collective fatigue ( Kim et al, 2020 ), and inhibit tumor metastasis ( Yun et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenosides have gradually attracted the attention of researchers, and their role in reversing immune-suppressive TME has received special attention (Sekar et al, 2022;Zhao et al, 2022). Increasing evidence shows that ginsenosides benefit the intestinal ecological environment of normal people and CRC patients and animals (Hou et al, 2022;El-Banna et al, 2022;Lei et al, 2022).…”
mentioning
confidence: 99%